Microbes: Mini Iron Factories - Joshi, Kumar Batuk (Indian journal of microbiology, 2014)
Microbes have flourished in extreme habitats since beginning of the Earth and have played an important role in geological processes like weathering, mineralization, diagenesis, mineral formation and destruction. Biotic mineralization is one of the most fascinating examples of how microbes have been influencing geological processes. Iron oxidizing and reducing bacteria are capable of precipitating wide varieties of iron oxides (magnetite), carbonates (siderite) and sulphides (greigite) via controlled or induced mineralization processes. Microbes have also been considered to play an important role in the history of evolution of sedimentary rocks on Earth from the formation of banded iron formations during the Archean to modern biotic bog iron and ochre deposits. Here, we discuss the role that microbes have been playing in precipitation of iron and the role and importance of interdisciplinary studies in the field of geology and biology in solving some of the major geological mysteries.